Plasticity of Leaf Respiratory and Photosynthetic Traits in Eucalyptus grandis and E. regnans Grown Under Variable Light and Nitrogen Availability - Kruse, Jörg; Turnbull, Tarryn; Rennenberg, Heinz; Adams, Mark A. (Frontiers in Forests and Global Change, 2020)
Plant growth strategies are adapted to resource availability in native habitat(s), and thus reflected in traits such as photosynthetic and respiratory capacities of leaves. We explored acclimation of such traits to contrasting light and nitrogen supply for Flooded Gum (Eucalyptus grandis) and Mountain Ash (E. regnans) saplings growing under warm-temperate conditions. We focused on respiration parameters that are not routinely measured, but could expand our mechanistic understanding of trait correlation networks (interdependencies between leaf mass per area (LMA), foliar nitrogen concentration (Nmass), photosynthetic capacity (mass- based Amax) and respiration (R)). We measured temperature responses of leaf R via calorimetric methods, in order to derive three respiration parameters that are useful to characterize capacity and flux mode of respiratory oxygen reduction in mature source leaves and young sink leaves. Subtropical E. grandis saplings produced three-fold more biomass than E. regnans, and responded more strongly to enhanced supplies of nitrogen, in particular under semi-shade conditions. Acclimation of LMA to growth irradiance was more plastic in E. grandis, but light treatment had no effect on Nmass and mass-based Amax in this species. In E. regnans, growth under abundant nitrogen and full sunlight caused significant increases in foliar Nmass – albeit not matched by relatively modest increases in mass-based Amax. Cool-temperate E. regnans saplings appeared to allocate a substantial share of leaf-N to protective functions upon exposure to full sunlight. Foliar nitrogen was used more effectively for the production of new foliage in E. grandis, owing to better coordination with foliar capacity and flux mode of mitochondrial oxygen reduction. Most of the variation in three respiration parameters can be explained by a few physiological/anatomical variables, responding to variation in absolute and relative demand for ATP, reducing power and anabolic intermediates. These demands strongly depended on leaf developmental stage and also varied between species and treatments. Our approach opens a path to improved process- based understanding of respiratory flux control, which could facilitate predictions of plant respiration in a changing environment.